The Method of Teaching Russian Language through Translations of Proverbs and Phraseological Expressions - Kaloh Vid, Natalia (Slavia Centralis, 2024)
The present article focuses on the use of proverbs and phraseological expressions in the course The Lectorate of the Slavic Language - Russian and suggests translation activities that should help students improve their knowledge of the Russian language by reading, translating, analyzing and discussing proverbs. This method was used in the second part of the 60-hour elective course The Lectorate of the Slavic Language - Russian, once the students were familiar with the Cyrillic alphabet and were able to read short sentences. The students focused primarily on recognizing and translating the components of Russian phraseological expressions and proverbs. Some of the proverbs were similar to Slovene ones. The aim of the activity was to stimulate the students’ interest in a foreign cultural environment and to enable them to use their existing knowledge of the foreign language and their imagination instead of dictionaries and glossaries. In the second phase of the activity, students presented their translation solutions and ideas and shared their experiences with the professor who also offered explanations of the meanings of the proverbs and phraseological expressions.
Keywords: Russian language, translation, teaching, proverb, phraseological expression